Public Sentiment Analysis on the Boycott Israel Movement on Platform X Using Random Forest and Logistic Regression Algorithms - Agustin, Rachmayanti Tri; Cahyana, Yana; Baihaqi, Kiki Ahmad; Rohana, Tatang (Politeknik Negeri Batam, 2025)
This research aims to analyze public sentiment toward the boycott movement against Israel on the X platform by applying Random Forest and Logistic Regression algorithms. The study uses 616 tweets collected through web crawling with relevant keywords such as